Comparative Transcriptome and Proteome Analysis of Heat Acclimation in Predatory Mite Neoseiulus barkeri - Tian, Chuan Bei; Li, Ya Ying; Huang, Ji; Chu, Wen Qiang; Wang, Zi Ying; Liu, Huai (Frontiers in Physiology, 2020)
In our previous study, we reported a high temperature adapted strain (HTAS) of the predatory mite Neoseiulus barkeri was artificially selected via a long-term heat acclimation (35°C) and frequent heat hardenings. To understand the molecular basis of heat acclimation, ‘omics’ analyses were performed to compare the diﬀerences between HTAS female adults to conventional strain (CS) at transcriptional and translational levels. We obtained a total of 5,374 diﬀerentially expressed genes and 500 diﬀerentially expressed proteins. Among them, 119 transcripts had concurrent transcription and translation profiles. It’s conserved that some processes, such as high expression of heat shock protein (HSP) genes, involved in heat tolerance of transcriptome analyses, while many protective enzymes including glutathione S-transferase, superoxide dismutase, peroxidase and cytochrome P450 displayed down-regulated expression. KEGG analysis mapped 4,979 and 348 diﬀerentially expressed genes and proteins, to 299 and 253 pathways, respectively. The mitogen-activated protein kinases (MAPK) signaling pathway may provide new insights for the investigation of the molecular mechanisms of heat tolerance. Correlation enriched pathways indicated that there were four pathways associated with heat acclimation involving in energy metabolism and immunity. In addition, the expression patterns of ten randomly selected genes including HSP were consistent with the transcriptome results obtained through quantitative real-time PCR. Comparisons between transcriptome and proteome results indicated the upregulation of HSPs and genes participated in ATP production, immunity and energy metabolism process. A majority of antioxidant-related genes and detoxication-related genes were downregulated suggesting a fitness cost of heat acclimation. Our results demonstrated that heat tolerance during a long-time acclimation of N. barkeri is a fairly complicated process of physiological regulations. These findings also contribute to a better understanding of the mechanisms of thermal responses of phytoseiid mites which clould provide useful information for biological control through natural enemies.